Thermal and wear properties of sansevieria trifasciata green fiber–carbon fiber polymer hybrid composite - Sandhya Rani Borukati; B Durga Prasad; A Ramesh; K Anbumani (Materials Research Express, 2021)
The composites of the recent era have replaced the conventional materials which are widely used in the aerospace industry and safety applications. These application areas require high strength and tough structural materials. Hybridization of natural and synthetic fibers reduces cost, weight, and environmental effects caused by synthetic fiber composites without compromising its strength. In the present study Sansevieria Trifasciata Fiber (S.T.F) and Carbon Fiber (cf) reinforced hybrid composite materials were developed and subjected to wear analysis, Thermo Gravimetric Analysis (T.G.A), Differential Thermo Gravimetric (DTG) analysis, Scanning Electron Microscope (S.E.M.) for micro structure . The hybrid composites were prepared through the manual hand layup process with different percentages of S.T.F. and cf T.G.A test was performed on the 63.5 × 12.7 × 3 mm ^3 samples. 30% S.T.F. and 70% cf hybrid epoxy composites under TGA reveals to have the content of 30.9% fiber loss, 67.8% resin loss and 2.2% ash content. 40% STF and 60% CF hybrid composite reveal to have 11.9% fiber loss, 87.2% resin loss and 1% ash content. Similarly 30% STF and 70% CF hybrid composite have the content of 25.8% fiber loss, 72.7% resin loss and 1.5% ash content. Specific wear index of approximately 0.0028062 mm ^3 /N-m was recorded for a sample of 40% STF and 60% CF and the minimum specific wear rate is 0.0010964 mm ^3 /N-m, recorded for a sample of 30% STF and 70% CF at 15 N. TGA contour confirmed that the fiber was solid below 250 °C with the highest cellulose decomposition temperature of 375 °C. DTG confirmed that the crystallization temperature of the fiber was found to be 480.5 °C and the decomposition of lignin was found to be 810 °C temperature.